Hot Work Tool Steel Processed by Laser Powder Bed Fusion: A Review on Most Relevant Influencing Factors. Issue 7 (8th May 2021) - Wu, Liang; Das, Suvajeet; Gridin, Witalij; Leuders, Stefan; Kahlert, Moritz; Vollmer, Malte; Niendorf, Thomas
Abstract : As a representative of a common carbon‐bearing hot work tool steel AISI H13 is in focus of the present review paper. Most relevant details for processing of AISI H13 by laser powder bed fusion (L‐PBF) are systematically investigated. Three common stages of process parameter development and material assessment, respectively, are in focus: general processibility, process refinement, and deduction of process–microstructure–property relations, i.e., understanding of the interplay of relevant elementary mechanisms. On the one hand, the routine of AISI H13 processing by L‐PBF is optimized for industrial application. This optimization includes laser parameters, heat treatment, and process sensitivity concerning the used machine and powder. On the other hand, the cluster‐like melt pool microstructure and the formation of various defects during L‐PBF processing of AISI H13 powder are under investigation. Most importantly, understanding of solidification cracking based on critical temperature regimes and residual stress cracking related to martensitic transformation is essential for robust process and material development for the L‐PBF process. Abstract : A literature review complemented by systematic experiments focusing on AISI H13 processed by laser powder bed fusion is presented. Process–microstructure–property relations are established, considering powder properties, preheating temperature, laser parameters, and heat treatment. Based on experiments focusing on various steels used for tooling, different types of defects are highlighted and rationalized based on underlying elementary mechanisms.